Аттестат профессионального роста учителя (Удмуртский университет, 2007)
Экземпляры: УКП (20081027) / Инвентарный номер: АП20070427 / Цена: / Сис.шифр: 74.204 / Авт.знак: А92 / ГРНТИ: 14 / ББК: 74.204.21